描述還是規範，政治還是倫理？——大疫當前的思考: Descriptive or Normative, Political or Ethical? - Some Reflections on the Challenges of the Pandemic - BAI, Tongdong (International Journal of Chinese & Comparative Philosophy of Medicine, 2020)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. In response to Ruiping Fan’s paper, I argue that his attribution of the relative success of East Asian states in dealing with the COVID-19 pandemic to Confucian culture is problematic in many respects. Some of his normative discussions based on Confucianism are too “thick” to be universal. His defense of the significance of ethics in the age of science, especially the appeal to the concept of synchronicity, and the use of filial piety to reject herd immunity are questionable. I argue that a Confucian hybrid regime that embraces liberalism and combines democratic elements with meritocratic elements may lead to better decision-making and that the Confucian’s New World System is a better alternative to globalization led by nation-states. DOWNLOAD HISTORY | This article has been downloaded 5 times in Digital Commons before migrating into this platform.